Membentuk pola pikir anti korupsi mahasiswa melalui pendidikan nilai islam dan pancasila - AL - AZAHRO, SHAKINAH BINTI (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that impacts social life, the economy, education, and national development in Indonesia. This study aims to analyze the role of Islamic and Pancasila values ​​education in shaping anti-corruption mindsets in university students. The research method used is a literature study by reviewing various journals and scientific sources related to anti-corruption education, Islamic values, and Pancasila values. The results show that anti-corruption education can shape students' character to be honest, disciplined, responsible, and have integrity. Islamic values ​​such as trustworthiness, honesty, justice, and piety play a vital role in building moral awareness to reject corruption. In addition, Pancasila values ​​also serve as the basis for developing anti-corruption attitudes through the values ​​of divinity, humanity, unity, democracy, and social justice. The formation of anti-corruption mindsets is not only carried out through theoretical learning, but also through habituation, role models, and academic culture in the university environment. Thus, Islamic and Pancasila values ​​education has a significant influence in shaping a young generation with integrity and anti-corruption.